2007
DOI: 10.1007/s10592-007-9453-5
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity of the Southwestern Atlantic humpback whale (Megaptera novaeangliae) breeding area off Brazil, and the potential connections to Antarctic feeding areas

Abstract: In the Southwestern Atlantic Ocean, humpback whales migrate every winter to the Brazilian coast for breeding and calving in the Abrolhos Bank. This breeding stock represents the remnants of a larger population heavily exploited during the beginning of the 20th century. Despite its relevance to conservation efforts, the degree of current genetic variation and the migratory relationship with Antarctic feeding areas for this population are still largely unknown. To examine these questions, we sequenced *400 bp of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 22 publications
7
55
0
2
Order By: Relevance
“…For example common minke whale B. acutorostrata from both sides of the Japanese archipelago (Sea of Japan and western North Pacific) are genetically differentiated . Genetic differentiation between animals in the west and east coast of South America has also been reported for other species such as the South American sea lion Otaria flavescens (Artico et al 2010), humpback whale Megaptera novaeangliae (Engel et al 2008) and dusky dolphins Lagenorhynchus obscurus (Cassens et al 2003), which reveals a common phylogeographic pattern.…”
Section: Population Differentiationmentioning
confidence: 54%
“…For example common minke whale B. acutorostrata from both sides of the Japanese archipelago (Sea of Japan and western North Pacific) are genetically differentiated . Genetic differentiation between animals in the west and east coast of South America has also been reported for other species such as the South American sea lion Otaria flavescens (Artico et al 2010), humpback whale Megaptera novaeangliae (Engel et al 2008) and dusky dolphins Lagenorhynchus obscurus (Cassens et al 2003), which reveals a common phylogeographic pattern.…”
Section: Population Differentiationmentioning
confidence: 54%
“…Example analysis of migration patterns among humpback whales sampling locations in the south seas: Olavarría et al (2007) and Engel et al (2008) described the interaction of several humpback whale populations (sampling locations). We use parts of their data to showcase how BF can inform the discussion of whether whales from these sampling locations belong to the same genetic population or not and whether some population models provide more appropriate descriptions than others.…”
Section: Tablementioning
confidence: 99%
“…Our analysis does not completely resolve the complex population interactions of humpback whales, but it shows ways in which our method is more useful than current methods for model comparisons. Engel et al(2008), using pairwise F ST estimates, suggested that Antarctic locations A1 and A2 appear panmictic; they used additional sighting data to suggest that the individuals sampled near the Brazilian coast probably do not move to the presumed feeding grounds in the Antarctic but instead aggregate at some unknown location. We chose a subset of models to investigate (1) whether the regions Antarctica 1 and 2 belong to a single population and (2) whether the Brazilian individuals and Antarctic individuals belong to the same population.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Baker et al 1998, Smith et al 1999, Calambokidis et al 2001, Stevick et al 2003, Constantine et al 2007, Engel et al 2008). This was due to a lack of scientific research on whales in the region.…”
Section: Introductionmentioning
confidence: 99%